Use of Prolactin Receptor Antagonist to Better Understand Prolactin Regulation of Pituitary Homeostasis - Ferraris, Maria Jimena (2013)
he anterior pituitary is permanently regulated by processes of apoptosis and proliferation in order to maintain tissue homeostasis. Several factors have been implicated in this regulation and lately, prolactin (PRL) has been included into that list. However, since PRL is secreted by anterior pituitary lactotropes, the actual outcome of its autocrine/paracrine actions on pituitary cells has remained difficult to assess. The availability of the pure PRL receptor antagonist Del1-9-G129R-hPRL has been helpful to circumvent this problem. While PRL has been traditionally associated with increased cell proliferation, recent studies revealed that this hormone actually induces apoptosis and decreases proliferation of anterior pituitary cells, by mechanisms involving the PRL receptor. The aim of this short review is to overview our current understanding of the regulation of pituitary homeostasis by PRL. Moreover, studies involving Del1-9-G129R-hPRL have helped anticipate to what extent future treatments involving PRL receptor inhibitors may interfere with processes regulated by PRL at the central level.